Read the digital fingerprints: log analysis for digital forensics and security. Issue 7 (July 2021) - Kara, Ilker
Abstract : Computers and other related computing systems – such as smartphones and tablets – are indispensable in our daily lives. Unfortunately, this attracts the attention of cyber attackers. Everyone is affected. Computer systems used in sectors as diverse as the defence industry, healthcare enterprises, the entertainment sector, banking and education have been targeted by illegal attacks.